Styling the self online: semiotic technologization in weblog publishing. Issue 5 (20th October 2018) - Adami, Elisabetta
ABSTRACT: Testing on digital semiotic production the concepts of (self-)styling and technologization of discourse, developed for offline linguistic phenomena, the article investigates the role of digital platforms in shaping the relation between self-expression online, semiotic regulation and the social construction of taste. By focusing on the use of semiotic resources of webdesign for identity expression, the study analyses the semiotic regimes emerging from regulatory practices and webdesign styles on WordPress, and their influence on the changes in the projected identity of a personal blogger. In spite of the participatory character of WordPress, results show the role of the platform in objectifying/technologizing hegemonic semiotic preferences, with consequent normalising effects in bloggers' self-styling practices. The conclusions relate the findings to broader power dynamics in the social construction of taste and their implications for both online and offline forms of self-expression.